Synthesis of Arylidene – Isoquinolinones bearing Combretastatin Skeleton by Cyclocarbopalladation/cross coupling Tandem Heck‐Suzuki Miaura Reactions using nano catalyst Pd@Py‐IL‐SPION. (12th December 2019) - Asgari, Mohammad Sadegh; Rashidi Ranjbar, Parviz; Rahimi, Rahmatollah; Mahdavi, Mohammad
Abstract : Cyclocarbopalladation/cross‐coupling cascade intramolecular Heck–Suzuki–Miyaura reactions is applied for the first time by palladium immobilized on pyridine‐imidazolium ionic liquid supported magnetic iron oxide nanoparticle catalyst (denoted Pd@Py‐IL‐SPION) for the last step to synthesize trisubstituted arylidene–isoquinolinones derivatives having Combretastatin skeleton. The reaction is performed via propargylamide intermediates prepared by Ugi 4‐CR reactions, which undergoes intramolecular Heck–Suzuki–Miyaura domino reaction to produce the desired trisubstituted arylidene‐isoquinolinones. The method shows full regio‐ and stereoselectivity derives from the particular Pd‐catalyzed syn ‐insertion of triple bond. Abstract : A Heck‐Suzuki Miaura Domino reaction is used for the first time by means of palladium immobilized on pyridine‐imidazolium ionic liquid supported magnetic iron oxide nanoparticle catalyst (denoted Pd@Py‐IL‐SPION) for synthesis of trisubstituted arylidene–isoquinolinones derivatives bearing Combretastatin skeleton. The stereochemistry of the synthesized materials derives from the particular Pd‐catalyzed syn ‐insertion of triple bond.